CT Analysis Demonstrates That Cochlear Height Does Not Change with Age - Mori, M.C.; Chang, K.W. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: CH measurements can often be useful in the diagnosis of inner ear malformations associated with SNHL. Our aim was to establish the relationship between CH and age by using analysis of CT images in patients who underwent coronal CT scans of the temporal bone between 2001 and 2007. MATERIALS AND METHODS: We measured CH on coronal CT scans of the temporal bone of 422 ears scanned from 2001 to 2007 in 211 patients, 1 month to 23 years of age. Using multivariate linear regression analysis, we determined the relationship of CH to age, sex, and HL type. In addition, 11 patients with multiple scans at different ages were assessed for change in CH with age. RESULTS: Average CH was 5.3 mm (normal range, 4.4–6.2 mm). Analysis showed no statistically significant change in CH across ages from 1 month to 23 years (95% CI for regression line slope = −0.003, 0.013). Likewise, there were no statistically significant differences in CH for patients with multiple scans at different ages. ICW increased with age as expected with increased cranial size. A small difference in CH between sexes was noted with males having greater CHs than females (P < .01). All patients with hypoplastic cochleas, defined by a CH <2 SDs from the mean (4.48 mm for males and 4.25 mm for females), had HL with a positive predictive value of 86%. CONCLUSIONS: CH does not change from 1 month of age to adulthood and is slightly greater in males than in females. CHcochlear heightCHLconductive hearing lossCIconfidence intervalHLhearing lossICWintercochlear widthSNHLsensorineural hearing loss